FINANCIAL CHARACTERISTICS OF SMALL AND MEDIUM ENTERPRISES (SMEs) IN PEKAN BARU - Rika Desiyanti (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
ABSTRACTThis study empirically analyses financial characteristics, namely the influence of economic knowledge of financial, attitudes, and financial experience on financial management behavior in Small and Medium Enterprises (SMEs) in Pekanbaru, Riau. This research is a quantitative study, and this study uses primary data obtained through questionnaires. The population in this study was SMEs in Pekanbaru, Riau. The sampling technique in this study is convenience sampling. After conducting the questionnaire distribution, the sample obtained was 131 questionnaires. Data processing and analysis using SEM-PLS analysis are processed using Smart-PLS software assistance. The study results show that financial knowledge, financial attitudes, and financial experience positively affect financial management behavior.Keywords: Financial Management Behavior, Financial Knowledge, Financial Attitude, Financial Experience, SMEs